Optimalisasi Sistem Pengendalian Internal dalam Mengurangi Tingkat Retur SP2D di Kantor Pelayanan Perbendaharaan Negara Kupang - Anastasia Barek Mukin; Maria Prudensiana Leda Muga; Minarni Anaci Dethan (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to determine and analyze the implementation of an internal control system based on COSO (Committee of Sponsoring Organizations of the Treadway Commission) theory, including the control environment, risk interpretation, control activities, information and communication, and optimized monitoring in reducing the rate of returns of Disbursement Orders Funds (SP2D) at the Kupang State Treasury Services Office (KPPN). The type of research carried out was descriptive analysis. The data sources in this research are primary data and secondary data. Primary data is used to obtain information that is directly relevant to the object of study from original sources, so that the data is more accurate and specific. Secondary data is used to support and compare research results through journals, books or other references. There were three informants in this study. The data analysis technique used is the theory of Milles and Huberman. The results of this research indicate that the implementation of the internal control system at KPPN Kupang is not fully in accordance with the indicators outlined in COSO. KPPN Kupang does not have a Board of Commissioners and an Audit Committee and there are weaknesses in the information system used, namely there is no system validation that compares account data in the SAKTI application and banking data.